Subchronic inhalation toxicity of gold nanoparticles - Sung, Jae Hyuck (BioMed Central, 2011)
BACKGROUND: Gold nanoparticles are widely used in consumer products, including cosmetics, food packaging, beverages, toothpaste, automobiles, and lubricants. With this increase in consumer products containing gold nanoparticles, the potential for worker exposure to gold nanoparticles will also increase. Only a few studies have produced data on the in vivo toxicology of gold nanoparticles, meaning that the absorption, distribution, metabolism, and excretion (ADME) of gold nanoparticles remain unclear. RESULTS: The toxicity of gold nanoparticles was studied in Sprague Dawley rats by inhalation. Seven-week-old rats, weighing approximately 200 g (males) and 145 g (females), were divided into 4 groups (10 rats in each group): fresh-air control, low-dose (2.36 × 10(4 )particle/cm(3), 0.04 μg/m(3)), middle-dose (2.36 × 10(5 )particle/cm(3), 0.38 μg/m(3)), and high-dose (1.85 × 10(6 )particle/cm(3), 20.02 μg/m(3)). The animals were exposed to gold nanoparticles (average diameter 4-5 nm) for 6 hours/day, 5 days/week, for 90-days in a whole-body inhalation chamber. In addition to mortality and clinical observations, body weight, food consumption, and lung function were recorded weekly. At the end of the study, the rats were subjected to a full necropsy, blood samples were collected for hematology and clinical chemistry tests, and organ weights were measured. Cellular differential counts and cytotoxicity measurements, such as albumin, lactate dehydrogenase (LDH), and total protein were also monitored in a cellular bronchoalveolar lavage (BAL) fluid. Among lung function test measurements, tidal volume and minute volume showed a tendency to decrease comparing control and dose groups during the 90-days of exposure. Although no statistically significant differences were found in cellular differential counts, histopathologic examination showed minimal alveoli, an inflammatory infiltrate with a mixed cell type, and increased macrophages in the high-dose rats. Tissue distribution of gold nanoparticles showed a dose-dependent accumulation of gold in only lungs and kidneys with a gender-related difference in gold nanoparticles content in kidneys. CONCLUSIONS: Lungs were the only organ in which there were dose-related changes in both male and female rats. Changes observed in lung histopathology and function in high-dose animals indicate that the highest concentration (20 μg/m(3)) is a LOAEL and the middle concentration (0.38 μg/m(3)) is a NOAEL for this study.